2012
DOI: 10.1289/ehp.1104282
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Pathway Genes Belong to Major Targets of Persistent Organic Pollutants in Adipose Cells

Abstract: Background: Epidemiological studies emphasize the possible role of persistent organic pollutants (POPs) in obesity and the metabolic syndrome. These pollutants are stored in adipose tissue (AT).Objectives: Our aim was to study the effects of POPs on human adipose cells and rodent AT.Methods: Using human multipotent adipose-derived stem cells, we carried out large-scale gene expression analysis to identify the major pathways modified by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), polychlorinated biphenyl (PCB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 45 publications
3
114
0
10
Order By: Relevance
“…On the other hand, an in vitro study has suggested that LDL-receptors play a minor role in the cellular uptake of DDTlipoprotein complexes (Hjelmborg et al 2008). Since POPs have been described to be carcinogenic (National Toxicology Program 2006), affecting gene expression (Mitra et al 2012), be pro-inflammatory (Kim et al 2012) and to cause oxidative stress (Abdollahi et al 2004), they may, once inside the cells, contribute to the initiation of tumors as well as tumor progression. It is also possible that POPs may alter LDL function through effects on apolipoproteins (Arehart et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an in vitro study has suggested that LDL-receptors play a minor role in the cellular uptake of DDTlipoprotein complexes (Hjelmborg et al 2008). Since POPs have been described to be carcinogenic (National Toxicology Program 2006), affecting gene expression (Mitra et al 2012), be pro-inflammatory (Kim et al 2012) and to cause oxidative stress (Abdollahi et al 2004), they may, once inside the cells, contribute to the initiation of tumors as well as tumor progression. It is also possible that POPs may alter LDL function through effects on apolipoproteins (Arehart et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is also associated with various health problems including musculoskeletal disorders (MSD), asthma, liver disease, and cardiovascular disease (CVD) (7)(8)(9)(10). Moreover, neurohormonal and endocrine pathway disruption has been associated with obesity (11,12). Work factors, including sedentary work and taskrelated biomechanics, have been reported as risks for obesity (13)(14)(15).…”
mentioning
confidence: 99%
“…PCB'lerin birikme eğilimleri yüzünden insanlar su kaynaklarında bulunan miktarın çok daha yüksek miktarlarına maruz kalmaktadır. 27,28,[31][32][33][34] POLİKLORLU BİFENİLLER VE DOZ KAVRAMI Düşük doz PCB maruziyetinin vücut ağırlığı ile doğru orantılı olduğu; yüksek doz PCB temasının ise ters orantılı olduğu bildirilmiştir. Bu kimyasal maddelerin obezite üzerine etkileri doz, maruziyet dönemi, cinsiyet ve kimyasal yapısına bağlı olarak değişiklik göstermektedir.…”
Section: Poli̇klorlu Bi̇feni̇lleri̇n Kullanim Alanlariunclassified
“…Bu kimyasal maddelerin obezite üzerine etkileri doz, maruziyet dönemi, cinsiyet ve kimyasal yapısına bağlı olarak değişiklik göstermektedir. 34 Yapılan son çalışmalarla, az klorlanmış PCB'lerin obeziteyle çok fazla ilişkilendirilmediği ve doz-yanıt eğrilerinin ters U şeklinde olduğu belirlenmiştir. Diğer taraftan, çok klorlanmış PCB'lerle obezite arasında ters ve daha anlamlı bir ilişki olduğu bulunmuştur.…”
Section: Poli̇klorlu Bi̇feni̇lleri̇n Kullanim Alanlariunclassified